The cell wall of hornworts and liverworts: innovations in early land plant evolution?. (26th April 2022) - Pfeifer, Lukas; Mueller, Kim-Kristine; Classen, Birgit
Abstract: An important step for plant diversification was the transition from freshwater to terrestrial habitats. The bryophytes and all vascular plants share a common ancestor that was probably the first to adapt to life on land. A polysaccharide-rich cell wall was necessary to cope with newly faced environmental conditions. Therefore, some pre-requisites for terrestrial life have to be shared in the lineages of modern bryophytes and vascular plants. This review focuses on hornwort and liverwort cell walls and aims to provide an overview on shared and divergent polysaccharide features between these two groups of bryophytes and vascular plants. Analytical, immunocytochemical, and bioinformatic data were analysed. The major classes of polysaccharides—cellulose, hemicelluloses, and pectins—seem to be present but have diversified structurally during evolution. Some polysaccharide groups show structural characteristics which separate hornworts from the other bryophytes or are too poorly studied in detail to be able to draw absolute conclusions. Hydroxyproline-rich glycoprotein backbones are found in hornworts and liverworts, and show differences in, for example, the occurrence of glycosylphosphatidylinositol (GPI)-anchored arabinogalactan-proteins, while glycosylation is practically unstudied. Overall, the data are an appeal to researchers in the field to gain more knowledge on cell wall structures in order to understand the changes with regard to bryophyte evolution. Abstract : This review summarizes and discusses current knowledge on hornwort and liverwort cell walls and highlights the similarities and differences in the light of plant evolution and terrestrialization.